Coconut wood as raw material for table making / Khairuddin Ahmad Jamaluddin - Ahmad Jamaluddin, Khairuddin (2003)
Coconut wood (Cocos nucifera Lynn), is used as raw material in table making. Coconut wood is a species of Palmaceae family which is less used in wood based industries today. The manufacturing process started from tree felling until table constructing. Sketches process and drawing translation to finish product also contributed in table manufacturing realization. Methods to produce coconut wood as new useful features are important as new alternatives for existence wood. This manufacturing process also proven that coconut wood can be used as raw material for furniture making. Any problem or mistakes encountered from the design can be detected and corrected for further improvement by others. The finish product can be proven that the successful table manufacturing process with coconut wood.